Changes in lifestyle upon diagnosis of cancer or other chronic illnesses: A Turkish Oncology Group study - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2018)
Cancer, like other chronic illnesses, changes the patients' way of living significantly. Although some may think, for instance, that religiousness would increase with the diagnosis of cancer, no previous studies have been performed in the Turkish society to confirm this. We, as the Turkish Oncology Group, conducted a survey in seven different oncology centres, representing a large majority of Turkey, to investigate how patients' lifestyles changed following a cancer diagnosis; we used dialysis patients as a chronic illness control group. The study findings showed how changes in spiritual practices are completely in line with what is observed in other chronic illnesses. These findings may help to address cancer patients' needs and facilitate resource allocation accordingly.
Keywords: cancer; chronic illness; lifestyle; religion; spirituality; BREAST-CANCER; SPIRITUALITY; RELIGION; CARE; ILL